Table of Content - - (Journal of Islamic Sciences, 2024)
Table of Content: 1. Achieving a chapter (prayer conditions) in the Sunni talents book explanation of the urban introduction of Sheikh Said Baishen Mr. Mohammed Jamal Mohammed Al-Sagaf 2. Meanings of victory in the Holy Qur’an and its causes Mr. Ibrahim Hammad Yousef Odeh